Man of the hour : a novel - Blauner, Peter (London : Fourth Estate, 1999)
David teaches at the multi-racial Coney Island High School in New York. When a bomb explodes aboard the bus taking his class on a museum outing, David rescues a student and becomes a media star, a hero to his pupils. But then a twist of fate transforms him into the prime suspect for the bombing
Keywords: Fiction